NEW FOREIGN EXCHANGE POLICY MECHANISM FOR NATURAL RESOURCE EXPORTS IN 2025: IMPLICATIONS AND CHALLENGES - tua, maruli_tua (Pusat Unggulan Ipteks-PUI Universitas Jambi, 2025)
This article analyzes the new policy on the management of foreign exchange earnings from the export of natural resources (SDA) as regulated under Government Regulation Number 8 of 2025, which will be implemented starting in 2025. The policy mandates exporters to place 100% of their export foreign exchange proceeds within the national financial system for a minimum period of 12 months. The primary objectives of this regulation are to strengthen Indonesia’s foreign exchange reserves, maintain the stability of the rupiah exchange rate, and reduce dependence on foreign debt. The policy applies to several strategic sectors, including mining (excluding oil and gas), plantations, forestry, and fisheries. Its implementation is expected to generate positive impacts, particularly in increasing foreign exchange reserves and fostering a more stable and conducive investment climate. However, the policy also presents challenges, especially in relation to liquidity management and cash flow constraints for exporters, particularly small and medium-sized enterprises. To support compliance, the government offers various incentives, such as competitive interest rates, tax incentives, and access to financing facilities based on export foreign exchange funds. Additionally, the reporting and supervisory mechanisms involving relevant authorities will be strengthened to ensure transparency and effectiveness. This article discusses the policy’s mechanisms, implications, and challenges, and provides recommendations to support effective implementation and sustainable economic development in Indonesia.